Eco-P: Eco-Friendly Printer / Nur Hazwani Mohamad Roseli … [et al.] - Mohamad Roseli, Nur Hazwani; Suhaili, Muhammad Shahrin; Paijan, Nur Syafiqah; Sukiman, Nur Anthasha; Zakaria, Natrah Adilla; Dzulkifly, Sofiah Haiza (Division of Research and Industry Linkages, 2017)
In this era, printer is one of the important device which makes a persistent human-readable representation of graphics or text on paper or similar physical media. Not only printer but scanner and photocopy machines are also very important equipment to most people regardless organizations or individual. With the advancement of technologies in nowadays world, ECO-P is a new "Portable Eco-friendly Printer” is an initiative to improve the existing types of printer that available in the market. Moreover, this device is suitable for travel and easy access especially for freelancer and students anytime and anywhere. There are several problems regarding existing printers such as too costly, required many space and difficult to bring to anywhere. Different from the current available printer, our product is used by solar energy. ECO-P does not require ink because it is using ‘tanning’ concept. Besides, it also can easily access through smartphone or screen that is available on the product. About the function, this device has a small screen at the top of the device whereby it can trace any documents transferred into it. Besides, the screen displayed a few buttons that can change the mode of functions whether the user want to use it as print, scan, photocopy or even fax. This device not only can be connected by USB port but also through Wi-Fi, Bluetooth or Air Drop. The uniqueness function of this device is it can store the solar energy at the bottom of the device and can be used even at night time. Based on these specification, this product can be commercializing because it has multifunction, eco-friendly and saving-cost.